A STUDY OF THE IMPACT OF THREE DAY TRAINING PROGRAMME ON KNOWLEDGE REGARDING BIOMEDICAL WASTE AMONG PARAMEDICAL STAFF OF DISTRICT HOSPITAL ETAWAH (UP) - Srivastava, Dhiraj Kumar; Ansal, Manoj; Gour, Neeraj; Chaduary, Pooja; Jain, Pankaj Kumar; Chouksey, Mahendra; Pathak, Pawan (Indian Journal of Community Health, 2013)
Introduction: Biomedical waste by definition means “Any waste which is generated during the process of diagnosis, treatment or immunization of human or animal or in research activities pertaining there to in the production or testing of biological”Objectives:• The level of awareness about various aspect of Bio Medical Waste management among the paramedical staff.• To study the impact of three day training programme on knowledge of Bio Medical Waste management. Material & Methods: The present study is a Cross sectional Study carried out to assess the impact of three day training programme on knowledge of Paramedical staff posted at District Hospital, Etawah. The change in knowledge was assessed using pre- test and post- test questionnaire.Result: A total of 72 paramedical staff participated in the study. Majority of the participants were unaware about the hazards associated with the improper handing f Biomedical wastes. The knowledge about the different color codes used for the segregation of biomedical waste was also very low. Similarly, the awareness about the vehicle used for the transportation of biomedical waste was also poor.Conclusion: The present study concludes that there is an urgent need for regular training for paramedical staff posted at District Hospital and other government hospital located in small District & town as awareness about the Biomedical waste among them is very low.